2011
DOI: 10.1080/00480169.2011.605747
|View full text |Cite
|
Sign up to set email alerts
|

Mycobacterium aviumsubsp.paratuberculosisinfection in wildlife on three deer farms with a history of Johne's disease

Abstract: Previous studies overseas have postulated a role of wildlife as reservoirs of Map infection and possible vectors of Johne's disease to livestock. Here, brushtail possums, hedgehogs and rabbits and in particular were identified as potential wildlife hosts for Map infection in New Zealand. This suggests that several wildlife species could contribute to the persistence of Map infection within a wildlife/livestock complex, and potentially, perhaps more importantly, to the spread of infection between farms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
21
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 21 publications
0
21
0
Order By: Relevance
“…, bezoar (Capra aegagrus) (27) (Kopecna et al, 2006), chamois (Rupicapra rupicapra) (134) (Kopecna et al, 2006), hawk (1) (Florou et al, 2008), owl (1) (Florou et al, 2008), Spur-winged plover (1) (Nugent et al, 2011), wolf (1) (Florou et al, 2008), duck (1) (Whittington et al, 2003). M. paratuberculosis was cultured in all samples for Eurasian Otter (n=2) (Matos et al, 2013), Common snipe (1) (Corn et al, 2005), Tapir (1), Okapi (1), Gayal (1), Blesbok (3), Banteng…”
mentioning
confidence: 99%
“…, bezoar (Capra aegagrus) (27) (Kopecna et al, 2006), chamois (Rupicapra rupicapra) (134) (Kopecna et al, 2006), hawk (1) (Florou et al, 2008), owl (1) (Florou et al, 2008), Spur-winged plover (1) (Nugent et al, 2011), wolf (1) (Florou et al, 2008), duck (1) (Whittington et al, 2003). M. paratuberculosis was cultured in all samples for Eurasian Otter (n=2) (Matos et al, 2013), Common snipe (1) (Corn et al, 2005), Tapir (1), Okapi (1), Gayal (1), Blesbok (3), Banteng…”
mentioning
confidence: 99%
“…Farmers also need to assure that the pastures are properly fenced so that the livestock are kept in the pastures, and predators and other wildlife that might share pathogens are kept out of the pastures. For example, wild ruminants and other wild non-ruminants (e.g., rabbits) can harbor and shed MAP [13,15,16]. The presence of deer on the farm has been associated with increased odds of being JD positive [79].…”
Section: Nutritionmentioning
confidence: 99%
“…MAP has been shown to infect a wide variety of domestic and wild ruminants such as cattle, sheep, goats, deer [13,14] and mouflons [13]. However, they have also been isolated from monogastric mammals such as rabbits [13,15,16] and hedgehogs [15], as well as from wild birds residing close to or on farm property [15].…”
Section: Etiology and Epidemiologymentioning
confidence: 99%
“…Rabbit, deer and other wildlife have also been shown to be infected by Map (Waddell et al, 2016). While various species of wildlife can act as a reservoir of Map (Nugent et al, 2011), the clinical symptoms of JD have only been observed in ruminants (Koets, Eda & Sreevatsan, 2015), camelids (Ghosh et al, 2012) and rabbits/hare (Beard et al, 2001). The symptoms of JD in infected animals are highly similar to those of Crohn’s disease in humans, where the absorptive surface of the gut is reduced due to thickening of the intestinal wall and other factors (Ott, Wells & Wagner, 1999).…”
Section: Introductionmentioning
confidence: 99%